2012
DOI: 10.1021/jp211109h
|View full text |Cite
|
Sign up to set email alerts
|

Growth Behavior, Lattice Expansion, Strain, and Surface Morphology of Nanocrystalline, Monoclinic HfO2 Thin Films

Abstract: Nanocrystalline HfO 2 films have been produced by sputter deposition under varying growth temperatures (T s ). The effect of T s , which is varied from room temperature (RT) to 500 °C, on the structural characteristics of HfO 2 films has been investigated employing X-ray diffraction (XRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). The results indicate that the monoclinic HfO 2 nanocrystals are highly oriented along the (1̅ 11) direction with increasing T s . The lattice expansion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 36 publications
2
47
1
Order By: Relevance
“…A similar inverse relationship has already been reported for several metal oxides -Al 2 O 3 , CeO 2 , Fe 2 O 3 , and HfO 2when they are on the nanoscale, [60][61][62][63][64] even if controversial and conflicting explanations have been proposed. Some authors suggested that this phenomenon could be caused by the Ti vacancy mechanism in rutile; 65 others attributed it to negative interface pressure, 66 yet others to the surface relaxation phenomenon.…”
Section: Lattice Volume Expansionsupporting
confidence: 73%
“…A similar inverse relationship has already been reported for several metal oxides -Al 2 O 3 , CeO 2 , Fe 2 O 3 , and HfO 2when they are on the nanoscale, [60][61][62][63][64] even if controversial and conflicting explanations have been proposed. Some authors suggested that this phenomenon could be caused by the Ti vacancy mechanism in rutile; 65 others attributed it to negative interface pressure, 66 yet others to the surface relaxation phenomenon.…”
Section: Lattice Volume Expansionsupporting
confidence: 73%
“…Transformation to the cubic polymorph having the fluorite structure occurs at 2600 C. It is evident, and well known, that the thermodynamically stability and phase existence depend on growth temperature and pressure conditions. [7][8][9][10][11][12][13][14][15][16][17] In addition, the controlled growth and manipulation of specific phase of HfO 2 at the nanoscale dimensions has important technological implications. Therefore, it is important to characterize and obtain a correlation between microstructure and optical properties in nanocrystalline HfO 2 films as a function of growth conditions.…”
mentioning
confidence: 99%
“…The crystalline domain size was calculated through the use of the Scherrer relationship. 8,15 X-ray reflectometry (XRR) measurements were performed on a Rigaku Smartlab X-ray diffractometer. Experimental data were then fit with the software package GlobalFit associated with Rigaku Smartlab diffractometer.…”
mentioning
confidence: 99%
“…The surface morphology of HfO 2 and changes in surface morphology of S-HfO 2 (after it was functionalised) were also observed by HRTEM which is showed in Fig. 8 It is clear that all the HfO 2 NPs aggregated and were amorphous, spherical like / interconnected with each other due to high stressed and temperature diffusion [33]. The particle size is ranged from 10 to 70 nm (Fig.…”
Section: Spectroscopic Characterization Of Hfo 2 and S-hfo 2 Nanoparticlesmentioning
confidence: 86%